A study on geotechnical behavior of stabilized peat soil with finite element modeling - Sii, Hee Yew (Universiti Malaysia Sarawak (UNIMAS), 2012)
(!eat or highly organic soils are well known for their high compressibility, natural moisture content, low shear strength and long-term settlement. Yet, Sarawak has the largest peat land area in Malaysia which is about 16,500 km2 or 13 % of the state land. There is very little data available from Sarawak regarding the geotechnical properties and behavior of local peat. In addition, the sampling of peat in undisturbed state is extremely difficult particularly at depths below the watertab~ In the current study of Sarawak peat an undisturbed peat sampler was designed and the sampling was executed in such a way that disturbance could be minimized. Peat samples were collected from Matang area of Sarawak. The effect of stabilizing natural peat with locally available ingredient, pond ash, was also explored. Pond ash is created from the disposal of fly ash. The wet disposal of fly ash into an ash pond is the most common fly ash disposal method. The compressibility characteristics of local undisturbed peat soil are examined through oedometer and Rowe cell testing of undisturbed samples. The experimental results were compared with available published data on Malaysian peat. The material parameters obtained from experiments were used to perform a finite element analysis (PLAXIS) of shallow foundations placed on deposits of Sarawak peat soil. Three depths of peat layers, typically found in Sibu area of Sarawak were considered. The effect of stabilization was modelled by using a stability ratio (the normalized depth of stabilized layer using layer thickness) of 0, 0.25, 0.50, 0.75 and l.O. The model reveals that the use of pond ash in peat stabilization can significantly increase the soil bearing capacity. The results revealed that the stabilization was very significant at the very beginning of 2S % of peat depth. It was apparent that the working load of stabilized peat increased by 21 %, 28 % and 27 % in all 3 m, 7 m and 10m peat with a PA dosage of 2S8 kg/m3 for 2S % of peat depth. Furthermore, the use of PA in soil stabilization helps in reducing the pond volume and achieving an environmental-friendly as well as a sustainable development of natural resources.